2018
DOI: 10.1186/s12947-018-0129-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of basic transesophageal echocardiography in hemorrhagic shock: potential applications during resuscitative endovascular balloon occlusion of the aorta (REBOA)

Abstract: BackgroundThere are numerous studies in the cardiovascular literature that have employed transesophageal echocardiography (TEE) in swine models, but data regarding the use of basic TEE in swine models is limited. The primary aim of this study is to describe an echocardiographic method that can be used with relative ease to qualitatively assess cardiovascular function in a porcine hemorrhagic shock model using resuscitative endovascular balloon occlusion of the aorta (REBOA).MethodsMultiplane basic TEE exams we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…However, the extent of this change has never been rigorously quantified, nor has the difference in afterload augmentation between pREBOA and fREBOA been described precisely. Echocardiography has been used to show changes in cardiac function with full REBOA in swine ( Teeter et al, 2018 ), but this is only an estimate within a narrow scope of cardiac biomechanical functional parameters. Other research has demonstrated that Esmolol during REBOA reduces myocardial injury ( Hoareau et al, 2020 ), suggesting that increased afterload is responsible for the cardiovascular effects and injury and that afterload modulation may be an approach to ameliorating the myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of this change has never been rigorously quantified, nor has the difference in afterload augmentation between pREBOA and fREBOA been described precisely. Echocardiography has been used to show changes in cardiac function with full REBOA in swine ( Teeter et al, 2018 ), but this is only an estimate within a narrow scope of cardiac biomechanical functional parameters. Other research has demonstrated that Esmolol during REBOA reduces myocardial injury ( Hoareau et al, 2020 ), suggesting that increased afterload is responsible for the cardiovascular effects and injury and that afterload modulation may be an approach to ameliorating the myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…At the mid-esophageal level, the probe was adjusted for ante exion and right rotation, and then, the left and right pulmonary vein views could be achieved at 30-50° and 100-120° respectively, and color Doppler was usually needed to assist in determining the acquisition of pulmonary veins. (7) At the mid-esophagus, other views could be acquired. From the long-axis view described in the preamble, advancing the probe could get the aortic valve LAX view when the aortic valve was put in the center of the frame with the angle range of 70-100°, and the aortic valve SAX view could be obtained at the angle of 30-50°.…”
Section: Transesophageal Echocardiographymentioning
confidence: 99%
“…Transesophageal echocardiography (TEE) and transthoracic echocardiography can provide important information regarding volume status, regional wall motion abnormalities, early diastolic dysfunction, and depressed contractility. 31 TEE can be included as part of an acute endovascular service, in the prehospital setting or used in austere environments when other imaging equipment is unavailable. TEE can specifically be used to evaluate aortic injury, cardiac tamponade, and identify the REBOA catheter tip location, which can facilitate placement in the operating room.…”
Section: Advancements and Innovationsmentioning
confidence: 99%
“…TEE can specifically be used to evaluate aortic injury, cardiac tamponade, and identify the REBOA catheter tip location, which can facilitate placement in the operating room. 31 The midesophageal inflow/outflow long and short view can identify the balloon position, demonstrate aortic dissection with identification of a false lumen, and assist the surgeon in safely deflating the balloon under direct visualization. 31 Prehospital healthcare providers should continue to focus on expedient transfer to the nearest endovascular or trauma facility.…”
Section: Advancements and Innovationsmentioning
confidence: 99%
See 1 more Smart Citation